Hospital readmission in persons with dementia: A systematic review. (20th May 2019) - Ma, Chenjuan; Bao, Silin; Dull, Peter; Wu, Bei; Yu, Fang
Abstract : Objective: Hospital readmission in persons with dementia is becoming a critical safety and cost issue. The purpose of this review is to systematically assess published evidence on hospital readmissions in persons with dementia, including rate, clinical reasons, risk factors, and prevention programs. Methods: A systematic review of relevant literature was conducted. Literature were searched in PubMed, CINAHL, PsycINFO, and Embase as well as hand searching. Quality of reviewed studies were assessed independently by reviewers using quality assessment checklists. Results: Nineteen studies met the inclusion criteria and were reviewed. In persons with dementia, all‐cause 30‐day readmission rate was most frequently reported and ranged from 7% to 35%. Compared with those without dementia, persons with dementia had significantly higher rate of readmission. Reported risk factors of readmission varied across studies from patient sociodemographic and clinical status, history of health care utilization, to family caregivers. Reasons for readmission were rarely documented. Programs of home‐based individualized care and interdisciplinary team care were used for preventing readmissions. Findings from some of the studies were limited by small sample sizes, single data source, and other methodologic flaws. Conclusions: Persons with dementia are at high risk for hospital readmission, but many of the readmissions are potentially preventable. Multiple strategies such like identifying high‐risk individuals and the clinical reasons for index admission and readmission and implementing home‐based individualized care by interdisciplinary team can reduce preventable hospital readmissions. Future studies should use multiple national data sources and advanced methodology to identify risk factors and clinical reasons of hospital readmissions.